Age, Gender and Duration of Dating with Involvement in Dating Violence - Suci Musvita Ayu; Erni Gustina; Mohammad Zen Rahfiludin (International Journal of Public Health Science (IJPHS), 2022)
Males and females tend to engage in Dating Violence (DV). This research aims to analyze the relationship between age, gender, and dating duration with the involvement of perpetrators of violence in dating. A cross-sectional study was used as the method. The sample size for this study was 351 adolescents who were selected using the purposive sampling technique. The sample inclusion criteria are active students, have a partner, and are willing to be respondents. Data were analyzed using a chi-square test with a 95% Confidence Interval. This study shows that younger adolescents are more likely to be involved in DV. Almost all females have acted as perpetrators of physical and psychological violence in dating. Females and males have equal opportunities to engage in dating violence. The dating duration is also predicted as one of the causes of adolescent involvement in violence during courtship. The dating duration is predicted to be more prone to being involved – being the perpetrator – in dating violence. Victims must have the courage to take a stand and stop the relationship if they experience violence, and they must be wise and selective in help-seeking.